Osteopontin‐integrin αvβ3 axis is crucial for 5‐fluorouracil resistance in oral squamous cell carcinoma. Issue 2 (10th December 2014) - Nakamura, Takuya; Shinriki, Satoru; Jono, Hirofumi; Ueda, Mitsuharu; Nagata, Masashi; Guo, Jianying; Hayashi, Mitsuhiro; Yoshida, Ryoji; Ota, Tomoko; Ota, Kazutoshi; Kawahara, Kenta; Nakagawa, Yoshihiro; et al.
Abstract : Clinical applications of a chemotherapeutic agent, 5‐fluorouracil (5‐FU) in oral squamous cell carcinoma (OSCC) have been limited because of drug resistance. This study aimed to identify novel mechanisms of 5‐FU resistance. Here we found increased osteopontin (OPN) gene expression in OSCC tissues with resistance to 5‐FU‐based chemoradiotherapy. OPN overexpression in OSCC cells led to 5‐FU resistance and abrogated the prosurvival effect of the drug in a mouse xenograft model. OPN‐induced 5‐FU resistance required integrin αv β3 . Targeting integrin αv β3 reversed the resistance in a 5‐FU‐resistant clone highly expressing OPN. Our data suggest that the OPN‐integrin αv β3 axis is crucial for 5‐FU resistance in OSCC. Abstract : OPN gene expression is increased in OSCC tissues with 5‐FU resistance. OPN overexpression in OSCC cells leads to 5‐FU resistance. OPN‐induced 5‐FU resistance requires integrin αv β3 activity. Targeting integrin αv β3 reverse the acquired 5‐FU resistance in OSCC cells.